Current methods of rehabilitation after arthroscopic reconstruction of the anterior cruciate ligament of the knee joint (review of literature) - Ildar F. Akhtyamov (Гений oртопедии, 2021)
Introduction The leading method for treating patients with injuries of the anterior cruciate ligament is its reconstruction. Although this operation is a common procedure, the issues of rehabilitation have not been fully studied. The aim of study Collection and analysis of available published studies on current methods of rehabilitation treatment after arthroscopic reconstruction of the anterior cruciate ligament. Materials and methods We analyzed the publications that were devoted to current methods of rehabilitation treatment of patients after arthroscopic reconstruction of the anterior cruciate ligament. The materials were searched for in the PubMed and Web of Science databases using the keywords “anterior cruciate ligament reconstruction”, “anterior cruciate ligament rehabilitation”. Inclusion criteria were compliance with the general topic, relevance, introduction of new rehabilitation treatments. Studies published earlier than the last 10 years were excluded. Results The analysis found that the main rehabilitation treatments used in patients after reconstruction of the anterior cruciate ligament are of protective character (wearing a functional orthosis or other immobilizing appliance, dosed walking with crutches) and physical activity (complex of exercises, swimming). The most effective way to prevent contractures is early activation of the limb and the maintenance of muscle tone. In turn, the main task of immobilization is prevention or relief of pain. Our study proposes the authors’ methods of rehabilitation which can be used for restorative treatment and accelerate the process of ligament repair. The work includes rehabilitation procedures performed at home after reconstruction of the anterior cruciate ligament under the supervision of a rehabilitation instructor. Discussion Rehabilitation of patients after reconstruction of the anterior cruciate ligament is a necessary complement to surgical treatment. Fast recovery of patients and a full return to an active lifestyle depend on a proper rehabilitation program.